2019
DOI: 10.4103/ijnm.ijnm_134_18
|View full text |Cite
|
Sign up to set email alerts
|

Graves' disease with pancytopenia and hepatic dysfunction: A rare case presentation

Abstract: Pancytopenia due to thyrotoxicosis is a rare but serious complication. In this report, we describe a rare case of Graves’ disease confirmed on thyroid scintigraphy presented with coexisting pancytopenia and liver dysfunction. There was complete recovery of blood counts and hepatic enzyme level to normal after antithyroid treatment and radioiodine ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Several studies have reported not only neutropenia but pancytopenia as a complication of poorly controlled Graves’ disease ( 3 , 4 , 5 , 7 , 8 , 10 , 20 , 21 , 22 , 23 , 24 ) which responded to ATDs, with or without RAI. In one case report ( 10 ), although pancytopenia improved with ATDs, there was a recurrent increase in thyroid hormone levels and pancytopenia after four months, upon which subtotal thyroidectomy was performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported not only neutropenia but pancytopenia as a complication of poorly controlled Graves’ disease ( 3 , 4 , 5 , 7 , 8 , 10 , 20 , 21 , 22 , 23 , 24 ) which responded to ATDs, with or without RAI. In one case report ( 10 ), although pancytopenia improved with ATDs, there was a recurrent increase in thyroid hormone levels and pancytopenia after four months, upon which subtotal thyroidectomy was performed.…”
Section: Discussionmentioning
confidence: 99%
“…This has been reported several times in the literature, generally in the adult population. Most of these patients were treated with thionamides, with blood counts improving after achievement of euthyroidism ( 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ). In particular, the presence of baseline neutropenia in a patient presenting with hyperthyroidism could be worrisome for the clinician, given the concern for potential agranulocytosis as a side effect of ATDs.…”
Section: Introductionmentioning
confidence: 99%